Application of a new type of Si–Al porous clay material as a solid phase support for immobilizing sp. PM3 to treat domestic sewage - Binhui Jiang; Yu Li; Haiyan Wang; Liping Jia; Fei Huang; Xiaomin Hu (Adsorption Science & Technology)
A novel Si–Al porous clay material W (reprocessed from ceramic waste) was used for Acidovorax sp. strain PM3 immobilization to promote the growth of strains and improve nitrogen and phosphorus removal performance in water treatment systems. The porous clay material W was characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy indicating that porous clay material W was a type of mullite with 63.52 m 2 /g specific surface area. After immobilization, the maximum biomass increased 2.7 times the specific growth rate and the removal rates of chemical oxygen demand (COD), ammonia (NH 4 + –N), and total phosphorus (TP) by the immobilized PM3 were 42.99, 29.19, and 11.76% higher than the free strain after 24 h. The Monod equation showed that the growth rate and processing speed of immobilized PM3 increased. The maximum adsorption capacities of COD and NH 4 + –N onto porous clay material W were 2.33 and 0.32 mg/g on the basis of Langmuir isotherm. The removal capacities of COD, NH 4 + –N, and TP by the immobilized PM3 were 588.24, 20.37, and 5.06 mg/l, respectively, as shown by kinetic studies. These results demonstrated that porous clay material W could improve the efficiency of microbial nitrogen and phosphorus removal, and the immobilized microorganism system could effectively treat domestic sewage. The adsorption isotherms can well describe the adsorption process. The maximum adsorption capacity of COD and NH 4 + –N on porous clay material W is 2.33 and 0.32 mg/g, respectively. Kinetic studies showed that the removal capacity of immobilized PM3 to COD, NH 4 + –N, and TP was 58.824, 20.37, and 5.06 mg/l, respectively.